Developing Learning Media of Adaptive Sport Course in SLLB Negeri 2 Padang - ai, erianti; Sari, Desi Novita (LPPM Undiksha, 2018)
In this study the problem was that the implementation of Penjasorkes learning was not maximum in SLB N 2 Padang. The implementation of Penjasorkes learning had not been success caused by a teaching strategy that was not appropriate with the condition such as the use of learning media that had not been able to provide physical education effectively and efficiently to students. So that it made the students were less creative and less motivated in doing physical activities, especially athletic material and the basic movements of running, throwing and jumping which were presented in the form of game. This research included development research that aimed to produce athletic learning media through playing with basic movements of running, jumping, and throwing for mentally retarded students at SLB N 2 Padang. Finally, this research was expected to contribute and be useful for the development of science especially in the field of physical education, sports and health. It could be concluded that there was a significant effect of the development of learning media on the basic athletic abilities of students in SLB N 2 Padang with an increase 3.49 in the average score, from the average score of pre test 50 and the post test 53.49.